Assessment of therapeutic effect of Inula heterolepsis boiss in alcoholic rats - (:unkn) unknown (WILEY, 2003)
An aqueous extract from the root of Inula heterotepsis Boiss was prepared and then tested for its ability to treat experimentally induced alcoholic hepatic injury in rats. Alcoholic rats were divided into two groups. The first group of rats were given 200 mg/kg/day plant extract. Repeated doses of extract preparations were given at 12 h intervals for 10 days. Differences between the recovery of tissue injury, with and without Inula plant extract, were evaluated. The second group of rats were given vehicle. Liver, testis and kidney injuries due to the chronic alcohol consumption were proven biochemically and histopathologically. Rats were killed, serum SGOT, SGPT, alkaline phosphatase, and albumin levels were measured. SGOT, SGPT and alkaline phosphatase levels were significantly higher in alcoholic rats due to the tissue damage compared with intact, vehicle and Inula treated groups of rats (p < 0.05). Liver, testis, kidneys, stomach, intestine, heart, lungs and bladder were examined histopathologically. According to our study, the root extract of Inula heterolepsis Boiss has a slight therapeutic effect on alcoholic liver, kidney and testis damage in rats. Comparing the therapeutic effects in these organs, the liver seemed to be affected meaningfully after treatment with the plant extract. Copyright (C) 2003 John Wiley Sons, Ltd.
Keywords: Inula heterolepsis boiss; hepatoprotective effect; alcoholic rats